Focus of attention instructions during baseball pitching training - Van der Graaff, E.; Hoozemans, M.; Pasteuning, M.; Veeger, D.; Beek, P. J. (International Journal of Sports Science & Coaching, 2018)
It has often been shown that performance and learning in movement tasks may be improved by focusing on the effect of the movement in the environment (external focus of attention) instead of the movement itself (internal focus of attention). Nevertheless, most coaching instructions and feedback information given in sports seem to favor an internal focus of attention over an external one. In the present study, we investigated coaches` instructions and feedback in an instrumental sports action, viz. baseball pitching, in which external targets are readily identifiable, such as the strike area or the catcher`s glove. To this end, we recorded and analyzed the pitching instructions and feedback statements of six baseball coaches given to 70 elite youth baseball pitchers (mean age 15.3 (SD 1.67) years) during regular pitching training sessions over a training period of four weeks. All instructions and feedback statements were classified according to the type of focus of attention invoked (i.e. internal or external), and a rest category of all other statements. Of the statements promoting a specific focus of attention (717/1699), only 31% (224/717) were classified as external focus of attention statements. Correspondingly, the responses on a questionnaire filled out by the pitchers indicated that they used an internal focus of attention during practice and preferred to receive internally oriented over externally oriented instructions and feedback. The present results show that, even in sports involving clear external targets such as baseball pitching, the internal focus of attention instructions prevails, the experimental evidence in favor of external focus of attention instructions notwithstanding.